2016
DOI: 10.1159/000442092
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anti-Noxa Antibody for Differential Diagnosis between Epithelioid Mesothelioma and Reactive Mesothelial Hyperplasia

Abstract: Objectives: The histological differential diagnosis between epithelioid mesothelioma (EM) and reactive mesothelial hyperplasia (RMH) is not always straightforward. The aim of the present study was to search for new immunohistochemical markers to distinguish EM from RMH. Methods: We evaluated and compared the expression of apoptosis-related genes in EM and RMH by real-time RT-PCR array analysis followed by clustering of significant gene expression. Immunohistochemical staining and statistical analysis of Noxa e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, sensitivity of Survivin labelling index (67.7%) and loss of BAP1 expression (66.2%) alone are not sufficient for differential diagnosis. Although diagnostic accuracies of Survivin (84.8%) and BAP1 (83.6%) as single markers were inferior to that of EMA (95.5%), ( 21 ) the diagnostic accuracy of the combination of Survivin and BAP1 (Survivin-positive and/or BAP1-loss) was 95.3%, which was almost similar to EMA. Recently, Shinozaki-Ushiku et al proposed using a combination of BAP1 and enhancer of zeste homolog 2 (EZH2) expression to differentiate between MM from RMH; the sensitivity of this combination was 90%, while the specificity was absolute ( 36 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, sensitivity of Survivin labelling index (67.7%) and loss of BAP1 expression (66.2%) alone are not sufficient for differential diagnosis. Although diagnostic accuracies of Survivin (84.8%) and BAP1 (83.6%) as single markers were inferior to that of EMA (95.5%), ( 21 ) the diagnostic accuracy of the combination of Survivin and BAP1 (Survivin-positive and/or BAP1-loss) was 95.3%, which was almost similar to EMA. Recently, Shinozaki-Ushiku et al proposed using a combination of BAP1 and enhancer of zeste homolog 2 (EZH2) expression to differentiate between MM from RMH; the sensitivity of this combination was 90%, while the specificity was absolute ( 36 ).…”
Section: Discussionmentioning
confidence: 83%
“…We recently reported that phorbol 12-myristate-13-acetate-induced protein-1 (PMAIP-1; Noxa) and baculoviral IAP repeat-containing 5 (BIRC5; Survivin) mRNA expression levels are significantly higher in EM than in non-neoplastic pleural tissue, and discussed the utility of anti-Noxa antibody for the distinction between EM and RMH ( 21 ). However, the utility of Survivin IHC for the differentiation of benign and malignant mesothelial proliferation has not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported the application of gene expression analysis to identify novel markers differentiating epithelioid mesothelioma from reactive mesothelial hyperplasia by PCR array. 8 Although gene expression analysis requires specimens with a high proportion of tumor cells containing good quality RNA, we successfully analyzed the RNA extracted from formalin-fixed paraffin-embedded samples.…”
mentioning
confidence: 99%
“…7 To develop our strategy for MPM, we selected a surface MPM cell marker that is suitable for nanoparticle targeting. Among published markers, [31][32][33] we identified CD146, a transmembrane glycoprotein belonging to the immunoglobulin superfamily, whose overexpression has been documented in several tumor cells (prostate, ovary, melanoma, and triple negative breast cancers) and linked to a poor prognosis. CD146 has been reported to not be expressed by normal or reactive mesothelium and is currently expressed in normal conditions by vascular endothelial cells and smooth muscle cells, with a recently identified role in the promotion of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%